Research Method and Variable of Finishing Study During Pandemic Time for English Language and Education Students - Handayani, Sri; Riyani; Ayuningtyas, Zahra Putri (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This social service aimed to (1) enhance students' understanding of qualitative research methods, (2) improve their grasp of research variables, and (3) provide solutions for students struggling to finish their studies during the pandemic. It used descriptive qualitative research to analyze how students designed research during the pandemic.Method: The study involved 20 English Language Education students from Universitas Slamet Riyadi. Data was collected through lectures, focus group discussions, and consultations. The team provided material on research methods and variables, discussed challenges in pandemic research, and conducted follow-up meetings for students to consult on their research.Practical Applications: Students initially faced difficulties in selecting research methods and variables, but the program helped them address these issues. They developed suitable research designs focused on qualitative methods and online learning, contributing new insights to university education during the pandemic.Conclusion: Based on the results and discussions from this social service, it can be concluded that solutions for students struggling to finish their studies during the pandemic were achieved through this activity. Theories, training, and intensive consultations helped students gain a clear understanding of how to conduct research effectively during the pandemic.